2013
DOI: 10.1002/j.1681-4835.2013.tb00401.x
|View full text |Cite
|
Sign up to set email alerts
|

ICT Barriers and Critical Success Factors in Developing Countries

Abstract: Since the early 1990s, Information and Communication Technology (ICT) has been perceived as a catalyst for development. However, the UNICEF State of the World's Children Report 2011 acknowledges that the poor in many developing countries remain largely excluded from ICT and its benefits. This paper aims to address three issues. Firstly, identify ICT barriers in the literature from 2000 to 2011. Secondly, identify ICT barriers through empirical findings and thirdly, categorize these barriers into critical succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 18 publications
(21 reference statements)
1
43
0
Order By: Relevance
“…The absence or inadequacy of infrastructure is a barrier to access among students in developing countries. Touray, Salminen and Mursu (2013) identified 43 ICT barriers in developing countries that were grouped into eight possible critical success factors, namely socio-cultural, infrastructural, political and leadership, legal and regulatory, economical, educational and skills, security and safety and technical. In Saudi Arabia, according to Al-Ghaith, Sanzogni and Sandhu (2010), the quality of the Internet was an important factor influencing the adoption and usage of e-learning.…”
Section: Implementation Of E-learningmentioning
confidence: 99%
“…The absence or inadequacy of infrastructure is a barrier to access among students in developing countries. Touray, Salminen and Mursu (2013) identified 43 ICT barriers in developing countries that were grouped into eight possible critical success factors, namely socio-cultural, infrastructural, political and leadership, legal and regulatory, economical, educational and skills, security and safety and technical. In Saudi Arabia, according to Al-Ghaith, Sanzogni and Sandhu (2010), the quality of the Internet was an important factor influencing the adoption and usage of e-learning.…”
Section: Implementation Of E-learningmentioning
confidence: 99%
“…Some specific challenges can be categorised using Touray et al (2013) CSFs: socio-cultural (telecentre not being adopted), educational and skills (required ICT skills not available), technical (insufficient resources) and infrastructural (access and privacy issues . Telecentres are also challenged by the fact that the role they play need to adapt as the challenges in their communities change over time (Bailey, 2009).…”
Section: Sustainability Of Telecentresmentioning
confidence: 99%
“…Limited ICT development in developing countries has been shown to restrict economic growth, with poor access to broadband services cited as a major contributor [1]. A major study into these shortcomings in sub-Saharan Africa's broadband connectivity [2] found that backhaul networks are one of the reasons that broadband is not widely available in the region and remains a niche product, affordable by only a few.…”
Section: Introductionmentioning
confidence: 99%